Book of Job THE FAITHFUL JOB AND HIS JOURNEY TOWARD A DEEP AWARENESS OF WISDOM (JOB 42,1-6) - S.S.L., Paulus Halek Bere (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
The Book of Job is a profound piece of wisdom literature in the Old Testament, exploring themes of suffering, divine justice, and human righteousness. It is named after its central character, Job, a man described as